Pelatihan dan Pendampingan Penguatan Promosi Menggunakan Sarana Medsos di UMKM Kelurahan Pasar Keong Kabupaten Lebak, Rangkasbitung - Diana Triwardhani; Lina Aryani; Ranila Suciati (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING AND ASSISTANCE IN STRENGTHENING PROMOTION USING SOCIAL MEDIA FACILITIES IN MSMES IN PASAR KEONG VILLAGE, LEBAK REGENCY, RANGKASBITUNG. This Abdimas aims to provide training and assistance in terms of making promotional facilities on social media for MSMEs in Lebak Regency, namely in Pasar Keong Rangkasbitung Village. The chosen social media is Instagram, because for WhatsApp, on average, the trainees have already promoted there, so Instagram is an additional promotional media for them. There were 15 participants with various businesses, including wet cakes, chips, agricultural products, basic necessities and so on. They are very enthusiastic about participating in the training, because they are guided from the beginning of making Instagram to uploading their products.